Dialectological Value of the Version of the Armenian Epic “David and Mher”, Written by M. Abeghyan - Mesropyan, Haykanush; Hambartsumyan , Sasun (Bulletin of Yerevan University B: Philology, 2026)
This article presents the linguistic features of the version of "David and Mher" recorded by M. Abeghyan. This version of the Armenian epic was narrated to the renowned Armenologist by Nahapet of Moksa. Linguistic material from the last quarter of the 19th century has survived naturally, without scholarly processing. This version, which summarizes the rather complex phonetic and grammatical system and rich vocabulary of the Moksa dialect, has been comprehensively studied. The study revealed that the dialect possesses unique idioms, lexical units, and verb-adjective formations not found in other dialects of the region.Based on the accumulated data, it is proposed that the 21st century of Armenology will become a period of scientific analysis of the collected epic tales, evaluation of the work of scribes, the creation of a scientific center for the study of variants of tales, perpetuation of the memory and honoring of storytellers, as well as the publication of unpublished and rewritten versions with dialectal scientific transcription.  M. Abeghyan's recorded version of "David and Mher" offers extensive material for study not only by philologists but also by specialists in the history of language, dialectology, national psychophilosophy, and other disciplines. The Vatiant contains reliable and substantiated linguistic facts, particularly in its detailed examination of the phonetic, grammatical, and lexical features of the Moks dialect.Figurative expressions, phraseological units, adverbial structures, verb formations, atypical for the grammatical rules of the modern Armenian language, as well as numerous linguistic testimonies transmitted by Nahapet of Moks, testify to the skill of the scribe, to the scientifically based establishment of a connection between the specialist philologist and the narrator, to the desire to obtain from the speaker as much information as possible and to enrich the treasury of the Armenian language.
Keywords: epic; folklorist; storyteller; dialect; vocabulary; phonetics; variant; palatal vowel